The relationship between preoperative and postoperative neutrophil-lymphocyte and platelet-lymphocyte ratio with post-dural-puncture headache in patients undergoing cesarean section (Annals of Medical Research, 2021)
Aim: This study aims to evaluate whether there is a possible relationship between the preoperative and early postoperative period neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio and post-dural-puncture headache in patients undergoing cesarean section.Material and Methods: Two hundred twenty pregnant women scheduled to undergo elective cesarean section under spinal anesthesia, were studied. Patiens demografic data and blood count parameters were noted. Blood was sampled from a peripheral vein for neutrophil/lymphocyte ratio ve platelet/lymphocyte ratio. The time points for sampling blood were as follows: Preoperative; 1 day before and postoperative; within 6-12 hours after cesarean section. The patients were questioned for possible occurrence of spinal anesthesia induced headache on the first and seventh postoperative days. Post-dural puncture headache was evaluated according to the International Classification of Headache Disorders (ICHD-II) diagnostic criteria.Results: A total of 220 patients were enrolled in the study and 217 patients completed the investigation. Post-dural puncture headache was detected in 78 patients and the incidence was 35.9%. The measurements of laboratory parameters were statistically similar between two groups (P > 0.05).Conclusion: Our study results showed no relationship between the neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio, and post-dural-puncture headache in the preoperative and also, early postoperative period in patients who undergoing cesarean section.Keywords: Post-Dural-Puncture Headache; Neutrophil-Lymphocyte Ratio; Platelet-Lymphocyte Ratio; Cesarean Section.
Keywords: Post-Dural-Puncture Headache; Neutrophil-Lymphocyte Ratio; Platelet-Lymphocyte Ratio; Cesarean Section.